Biochemical and Functional Characterization of RNF213 (Mysterin) R4810K, a Susceptibility Mutation of Moyamoya Disease, in Angiogenesis In Vitro and In Vivo. Issue 7 (30th June 2015) - Kobayashi, Hatasu; Matsuda, Yoshiko; Hitomi, Toshiaki; Okuda, Hiroko; Shioi, Hirotomo; Matsuda, Tetsuya; Imai, Hirohiko; Sone, Masakatsu; Taura, Daisuke; Harada, Kouji H.; Habu, Toshiyuki; Takagi, Yasushi; et al.
Abstract : Background: P.R4810K of RNF213 (mysterin: rs112735431), which is an AAA + ATPase, is the susceptibility polymorphism for moyamoya disease (MMD) in East Asians. However, the role of RNF213 R4810K in the etiology of MMD is unknown. Methods and Results: To clarify the role of RNF213 in known angiogenic pathways, RNF213 expression was analyzed in endothelial cells (ECs) treated with several angiogenic and antiangiogenic factors, including interferons (IFNs). RNF213 was upregulated by IFN‐β through signal transducer and activator of transcription x in the promoter and mediated antiangiogenic activity of IFN‐β. RNF213 wild‐type (WT) overexpression could not lower angiogenesis without IFN‐β, but RNF213 R4810K overexpression could. To correlate biochemical function as ATPase and the role of RNF213 oligomer formation with antiangiogenic activity, we investigated the effects of mutations in the AAA + module. A mutation of the Walker B motif (WEQ), which stabilizes oligomerization, inhibited angiogenesis, but AAA + module deletion, which cannot initiate oligomerization, did not. Intriguingly, R4810K, similar to WEQ, decreased ATPase activity, suggesting its antiangiogenic activity through stabilizing oligomers. To confirm the antiangiogenic effect of RNF213 upregulation in vivo, vascular EC‐ or smooth muscle cell‐specific Rnf213 R4757K (R4810K ortholog) or WT transgenic (Tg) mice were exposed to hypoxia. Cerebral angiogenesis by hypoxia was suppressed in EC‐specific Rnf213 R4757K Tg mice, whereas it was not suppressed in other mice. Conclusions: This study suggests the importance of inflammatory signals as environmental factors and R4810K carriers for susceptibility to cerebral hypoxia. A specific inhibitor of ATP binding to the first AAA + could be a promising therapeutic candidate for MMD.